2018
DOI: 10.1016/j.biopsycho.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of caffeine on threat-selective attention: moderation by anxiety and EEG theta/beta ratio

Abstract: This further supports TBR as a marker of executive control and highlights the importance of taking baseline executive function into consideration when studying effects of caffeine on executive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 102 publications
(135 reference statements)
3
27
0
Order By: Relevance
“…TBR during rest was first associated with ADHD, 1,3 and later linked to various psychological functions and cognitive/emotional processes that rely on executive cognitive control, including trait and state AC, reversal learning, WM training, and control over automatic attentional threat biases. [10][11][12][13][14][15][16][17][18] The current results support the hypothesis that these relations reflect TBR dynamics occurring during the resting-state measurement that are caused by fluctuations in the balance between cognitive control and associative thought. Debriefing revealed that participants were mostly involved in thoughts about day-to-day issues and episodic memories or performance-interfering thoughts about experimental procedures when they lost count, confirming that the pre-button press periods represent periods of MW and thus loss of sustained attention toward the breath-counting task.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…TBR during rest was first associated with ADHD, 1,3 and later linked to various psychological functions and cognitive/emotional processes that rely on executive cognitive control, including trait and state AC, reversal learning, WM training, and control over automatic attentional threat biases. [10][11][12][13][14][15][16][17][18] The current results support the hypothesis that these relations reflect TBR dynamics occurring during the resting-state measurement that are caused by fluctuations in the balance between cognitive control and associative thought. Debriefing revealed that participants were mostly involved in thoughts about day-to-day issues and episodic memories or performance-interfering thoughts about experimental procedures when they lost count, confirming that the pre-button press periods represent periods of MW and thus loss of sustained attention toward the breath-counting task.…”
Section: Discussionsupporting
confidence: 85%
“…The observed relation between MW-related changes in TBR and ECN functional connectivity strengthens previous conceptualizations of TBR as reflecting voluntary top-down processes of EC (including AC), mediated by dlPFC, over bottom-up processes from limbic areas. 13,15,[69][70][71] For instance, recent studies from our laboratory reported that TBR moderated automatic attentional threat-biases as measured by a dot-probe task, 14,15 and by an emotional threat interference task 16 in the manner predicted by theories explaining the role of catecholamines in PFC-mediated executive functioning, 72,73 and theoretical models describing the role of cognitive control over such automatic attentional biases to threat (see Refs. 74 and 75).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations